2,4-Dihydroxy-5-Bromovalerophenone Oxime as a Gravimetric Reagent for Pd(II) and Mb(II) and Spectrophotometric Study of Complexes - Patel, N.B.; Desai, K.K. (Asian Journal of Chemistry, 2010)
2,4-Dihydroxy-5-bromovalerophenone oxime (DHBVO) was developed as a new analytical reagent for the gravimetric estimation of divalent palladium and manganese ions. In the pH range of 2.0 to 5.0, this reagent gives a golden yellow coloured precipitate with Pd2+. Job's method and mole ratio method revealed that the stoichiometry of the complex is 1 : 2. Beer's law is obeyed up to 63.78 ppm of Pd2+. The molar absorptivity at 440 nm of complex was found to be 5.01 x 102 L mol–1 cm–1 . The stability constant of the complex is found to be 2.45 x 109. Mn2+ gives dark green coloured precipitate in pH range 8.5 to 9.0. Using both the above-mentioned methods, it was found that stoichiometry was 1 : 1. The molar absorptivity at 420 nm was found to be 3.9 X 103 L mol–1 em–1. The stability constant of the complex is found to be 1.61 x 106. Beer's law is obeyed up to 6.60 ppm of Mn2+. The reagent can be used for the analysis of pyrolusite ore.